RETRACTED ARTICLE: QFFT quantum circuits for exact solutions of the black-hole singularity-mass schrödinger equations on quantum kerr- (A) ds galilean myers– perr driven gravitational transformations in a lorentzian path integral for the anti-COVID-19 roccuffirnatm, roccuttirnaTM, and eplerotiffirnaTM drug designs. Issue 1 (31st December 2022) - Grigoriadis, Ioannis
Statement of Retraction: We, the Editors and Publisher of the Cogent Engineering have retracted the following article: Ioannis Grigoriadis. QFFT Quantum circuits for Exact solutions of the Black-Hole Singularity-Mass Schrödinger Equations on Quantum Kerr- (A) Ds Galilean Myers– Perr driven Gravitational transformations in a Lorentzian Path Integral for the anti-COVID-19 RoccuffirnaTM, RoccuttirnaTM, and EplerotiffirnaTM drug designs. Cogent Engineering. 2022; 9(1):1-54. DOI: 10.1080/23311916.2022.2114198 Since publication, further assessment has determined there are substantial concerns related to the integrity of the content, and the article does not meet the expected editorial standards of the journal. The journal is committed to correcting the scientific record and will fully cooperate with any institutional investigations into this matter. The author has been informed of the retraction. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.